2021
DOI: 10.1002/fsn3.2603
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and antibiotic resistance of Shigella spp. isolates from food products

Abstract: The emergence of multidrug-resistant Shigella is a significant threat to global public health. Limited studies have investigated the incidence, antimicrobial susceptibility, and genetic diversity of Shigella isolated from food products. Conventional culturebased, serologic, molecular, disk diffusion, PCR, and RAPD-PCR methods were used to determine the prevalence rate, phenotypic and genotypic antibiotic resistance profile, and genetic diversity of the Shigella isolates from food samples including vegetable sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…This study found that resistance against trimethoprim-sulfamethoxazole, tetracycline, lineage III strains due to the acquisition of point mutations within the gyrA and parC genes (Hawkey, et al 2021, Phiri, et al 2021, Shad and Shad 2021. It is extremely important to monitor different S. sonnei lineages/sublineages and the antibiotic resistance profile of these strains as the new emerging threat to public health and global concern of food safety (Hawkey, et al 2021, Pakbin, et al 2021a, Pakbin, et al 2021c.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study found that resistance against trimethoprim-sulfamethoxazole, tetracycline, lineage III strains due to the acquisition of point mutations within the gyrA and parC genes (Hawkey, et al 2021, Phiri, et al 2021, Shad and Shad 2021. It is extremely important to monitor different S. sonnei lineages/sublineages and the antibiotic resistance profile of these strains as the new emerging threat to public health and global concern of food safety (Hawkey, et al 2021, Pakbin, et al 2021a, Pakbin, et al 2021c.…”
Section: Discussionmentioning
confidence: 94%
“…However, resistance against different antibiotics is becoming more common among the S. sonnei isolated from food and clinical samples. It is widely reported that some specific genotypes of S. sonnei are associated with high rates of multi-drug resistance and more frequently contribute to foodborne outbreaks (Pakbin, et al 2020a, Pakbin, et al 2021a, Ranjbar and Farahani 2019.…”
mentioning
confidence: 99%
“…Outbreaks of Sh. flexneri have been linked to unpasteurized vegetable juices and meat in recent years [ 35 , 36 ]. Eugenol had a bactericidal effect on Sh.…”
Section: Discussionmentioning
confidence: 99%
“…Shigella is a bacterium related with E. coli, which is classified into four serogroups according to their species: Shigella dysenteriae 1 (serogroup A), S. flexneri (serogroup B), Shigella boydii (serogroup C), and Shigella sonnei (serogroup D) (Jo et al, 2019;Pakbin et al, 2021). The serogroups from S. sonnei and S. flexneri are the most frequently isolated in vegetable salad samples (Pakbin et al, 2021). In animal cells, it has been found that the effector protein IpaB, secreted by the T3SS of S. flexneri, facilitates their adherence (Rasmussen et al, 2005) and the L-asparaginase (AnsB) protein is also necessary for the strain for full virulence (George et al, 2014).…”
Section: Other Microorganisms That Interact With Plantsmentioning
confidence: 99%